2006
DOI: 10.2225/vol9-issue5-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and stability studies of a lipase from thermophilic Bacillus sp: The effect of process parameters on immobilization of enzyme

Abstract: A thermostable lipase was partially purified from the culture supernatant of a thermophilic Bacillus sp. The enzyme is optimally active at 60ºC and pH 8.0. The enzyme showed enhancement in activity in presence of benzene or hexane (30% v/v each). The activity (assayed by determining the release of pNP from pNP laurate) was stimulated up to 60% of these solvents in enzyme reaction mixture. The catalytic properties of this thermostable enzyme can be further improved via the use of different immobilization techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 9 publications
(13 reference statements)
4
30
1
3
Order By: Relevance
“…The present report with 60% immobilization yield is almost ten times higher than that reported by Ghamgui et al 2004 where lipase from R. oryzae showed only 6.2% of total initial activity when adsorbed on unactivated silica [28]. Although only 50% immobilization yield was achieved with E. aerogenes lipases, which is less than the earlier report of Nawani et al 2006 but the present study of lipase immobilization on cross linked silica led to improved thermostability unlike the earlier report [29]. It was observed that the activated silica enhances the immobilization yield and thermostability of lipase, which may be due to the strong interaction between enzyme and the matrix.…”
Section: Resultscontrasting
confidence: 75%
“…The present report with 60% immobilization yield is almost ten times higher than that reported by Ghamgui et al 2004 where lipase from R. oryzae showed only 6.2% of total initial activity when adsorbed on unactivated silica [28]. Although only 50% immobilization yield was achieved with E. aerogenes lipases, which is less than the earlier report of Nawani et al 2006 but the present study of lipase immobilization on cross linked silica led to improved thermostability unlike the earlier report [29]. It was observed that the activated silica enhances the immobilization yield and thermostability of lipase, which may be due to the strong interaction between enzyme and the matrix.…”
Section: Resultscontrasting
confidence: 75%
“…Enzyme activity determined in the absence of metal ions was defined as 100%. In order to determine the effect of the some organic solvents on the esterase activity, organic solvents such as methanol, ethanol, isopropanol and acetonitrile at final concentration of 10% were added to the standard reaction mixture [14]. The residual activities were measured by comparison with standard assay mixture containing no organic solvent.…”
Section: Effects Of Different Metal Ions and Organic Solvents On Enzymentioning
confidence: 99%
“…Although the free enzyme was markedly inactivated (no detectable residual activities) at 80 °C for all times, the immobilized form preserved (36.11, 13.8 %) of its initial activity. This thermal inactivation might be due to the disturbance of globular structure of the protein by heat (Pahujani et al, 2008) or because immobilization provided more rigid external backbone for lipase molecules thus increasing the thermal stability of the immobilized lipase (Nawani et al, 2006). Also, the obtained data confirm the interaction between the support and the enzyme and this improves the enzyme stability (Ogino & Ishikawa, 2001;Ghamgui et al, 2004).…”
Section: Biochemical Properties Of the Free And Immobilized Lipasementioning
confidence: 55%